CCR5 receptor antagonists in preclinical to phase II clinical development for treatment of HIV - Kim, Michelle B. (Expert Opin Investig Drugs, 2016)
INTRODUCTION: The chemokine receptor CCR5 has garnered significant attention in recent years as a target to treat HIV infection largely due to the approval and success of the drug Maraviroc. The side effects and inefficiencies with other first generation agents led to failed clinical trials, prompting the development of newer CCR5 antagonists. AREAS COVERED: This review aims to survey the current status of ‘next generation’ CCR5 antagonists in the preclinical pipeline with an emphasis on emerging agents for the treatment of HIV infection. These efforts have culminated in the identification of advanced second-generation agents to reach the clinic and the dual CCR5/CCR2 antagonist Cenicriviroc as the most advanced currently in phase II clinical studies. EXPERT OPINION: The clinical success of CCR5 inhibitors for treatment of HIV infection has rested largely on studies of Maraviroc and a second-generation dual CCR5/CCR2 antagonist Cenicriviroc. Although research efforts identified several promising preclinical candidates, these were dropped during early clinical studies. Despite patient access to Maraviroc, there is insufficient enthusiasm surrounding its use as front-line therapy for treatment of HIV. The non-HIV infection related development activities for Maraviroc and Cenicriviroc may help drive future interests.